Can we predict the duration of COVID-19 pandemic? an observational analysis - Patra, Bijoy; Behura, Jharna; Dewan, Vivek; Yadav, T. P.; Datta, Vikram; Bahl, Dheeraj (International Journal Of Community Medicine And Public Health, 2020)
Background: Since the outbreak of 2019 novel corona virus pneumonia in the Wuhan city, China, the whole world has been ravaged by the pandemic of COVID-19. In this bleak scenario, China is witnessing the near cessation of the disease. The aim of the present study was to analyze the epidemiology curve of China and five other countries, and attempts to extrapolate these findings in the epidemiology curve of individual country to answer the question how long will the pandemic last on this globe. Methods: For the current study data from six countries namely China, Germany, Italy, South Korea Singapore, and India were considered. The resources for data collection were WHO Situation reports for corona virus disease (COVID-19), and Worldometer statistics for corona. Data were entered in to excel sheet and analyzed. Results: Data for total cases, active cases, death, recovery, inactive cases were analyzed for each country and construed in graphs. The epidemic curve of total cumulative cases in China can be observed to have four phases and the total duration of epidemic is around 24week±2 weeks. China is in last phase of the epidemic. In South Korea, Germany, Italy the epidemic curve of active and inactive cases has crossed each other and are in 3rd phase. India and Singapore are in phase 1. Conclusions: Despite the multitude of variables of COVID-19, the glimmer of hope for the end of pandemic can be inferred from the analysis of China, South Korea, Italy and Germany and can be extrapolated for India and Singapore.